Use of metallopolymers in molds for moulding of plastics - N. S. Pershin; M. S. Chepchurov (Вестник СибАДИ, 2017)
The authors consider the problem of using metallopolymers at reconstruction and repair of molds for plastics’ moulding. The authors compare physical properties of molds’ materials and metallopolymers. On the basis of the performed analysis, the authors have proposed some structural elements of molds for using metallopolymers. The article presents advantages and disadvantages of using metallopolymers in elements of molds.